2004
DOI: 10.1111/j.1469-8137.2004.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and physical mapping of Melampsora rust resistance genes in Populus and characterization of linkage disequilibrium and flanking genomic sequence

Abstract: Summary• In an attempt to elucidate the molecular mechanisms of Melampsora rust resistance in Populus trichocarpa , we have mapped two resistance loci, MXC3 and MER , and intensively characterized the flanking genomic sequence for the MXC3 locus and the level of linkage disequilibrium (LD) in natural populations.• We used an interspecific backcross pedigree and a genetic map that was highly saturated with AFLP and SSR markers, and assembled shotgun-sequence data in the region containing markers linked to MXC3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 76 publications
2
52
0
1
Order By: Relevance
“…For the MXC3 region, suppression of recombination has been shown in North American Populus species, similar to recent findings for the poplar sex determination region on chromosome XIX (Yin et al 2008). No NBS-LRR genes were found in the MXC3 region, but five putative resistance genes were identified, including two thaumatin-like pathogenesis-related proteins and three receptor-like kinases (Yin et al 2004;Germain and Séguin 2010). These pathogenesis-related (PR) proteins participate in plantinducible immunity via their accumulation in response to biotic or abiotic stress.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…For the MXC3 region, suppression of recombination has been shown in North American Populus species, similar to recent findings for the poplar sex determination region on chromosome XIX (Yin et al 2008). No NBS-LRR genes were found in the MXC3 region, but five putative resistance genes were identified, including two thaumatin-like pathogenesis-related proteins and three receptor-like kinases (Yin et al 2004;Germain and Séguin 2010). These pathogenesis-related (PR) proteins participate in plantinducible immunity via their accumulation in response to biotic or abiotic stress.…”
Section: Introductionsupporting
confidence: 86%
“…This block of low divergence on chromosome XIX is likely not only involved in sex determination but also in defense mechanisms: (a) the region contains the largest super cluster of NBS-LRR genes found in the Populus genome with 83 potentially encoding R-genes (Kohler et al 2008;Bresson et al 2011); This super cluster co-locates with Melampsora rust resistance loci MER, R1, and RUS in Populus deltoides × P. trichocarpa (Yin et al 2004;Jorge et al 2005;Bresson et al 2011); (c) the presence of 20 BEAF and DREF (BED finger) DNA-binding domains within Rgenes of this super cluster could speed up downstream signaling by direct regulation of transcription. Some of these BED-NBS-LRR genes were also found in the grapevine and rice genomes, but the extent of these chimeric proteins in poplar seems unique, and this gene family presents an exceptional diversity on chromosome XIX (Germain and Séguin 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, with a large root system maintaining water and P. deltoides Female 1,991.7 (145.6) 100.9 (13.9) 31.6 (4.2) 13.8 (1.6) 37.5 (6.0) 10.7 (3.8) 32.3 (6.7) P. nigra As determined by gas chromatography-mass spectrometry; retention time and key m/z are shown at the column headings; mean and SEM () of two male to six female replicate buds are shown within rows nutrient uptake and functioning to facilitate interannual store of carbon over multiple decades, the selective pressure to develop symbiotic interactions with soil microflora may be as strong as to develop pathogenic resistances. As an illustration, various loci controlling variation for both symbiosis levels and resistance have been identified in Populus (Zhang et al 2001;Yin et al 2004b;Jorge et al 2005;Tagu et al 2005;Kohler et al 2008;Duplessis et al 2009;Labbé et al 2011). Plants, in general, and Populus, in particular, have a variety of disease resistance genes (R) encoding proteins involved in the detection of pathogens and herbivores.…”
Section: Lrr Genesmentioning
confidence: 99%
“…Further studies revealed that the suppression of recombination was most likely caused by large hemizygous rearrangements (insertions/deletions) in one of the parents used for establishing the mapping population (Yin et al 2004). …”
Section: Possible Reasons For Suppressed Recombination At the Rrs2 Locusmentioning
confidence: 99%